Social media tools and its effect on secondary school students’ academic achievement in The Gambia - Shaib Emmanuel Oluwatobi; Jimoh Nurudeen Oluwaseun; Ramon Sikiru Adekunle (Technium Social Sciences Journal, 2020)
Since the innovation and widespread usage of the internet in this 21st century, social Media tools have been swiftly embraced by children, teens, youths, adult and old people in the universe. These tools have improved communication in the educational sector by creating unlimited opportunities for academic professionals and students in research thereby enhancing the teaching-learning process. In spite of the efficacy of social media tools in education, there are trepidations on the effect of these tools on student’s academic achievement. Findings shows that majority of the students make use of Facebook because majority of them have access to it which will make them addicted and distracted by online activities and thus have a detrimental impact on their academic achievement. To this end, this paper recommends that students should create a balance in lifestyle and academic activities hence, attention should be directed towards research to enhance their knowledge.